Differences in The Number of Germs in The Insertion Area of Central Venous Catheter (CVC) Done by Polyurethane Transparent and Plaster Gauze Dressing - Septiana Fathonah; Tri Wahyu Murni; Etika Emaliyawati (Jurnal Keperawatan Padjadjaran, 2018)
A central venous catheter is a catheter that is placed directly on a large vein in the body and its tip lies in one of the central veins that is often used on critical care patients. Colonization of bacteria (germ) around the insertion area of the CVC is an area that is very likely to cause infection even though it has been closed by dressing. The factor that should always be considered is that the state of moisture retention occurs beneath the dressing. Moisture will cause an increase in colonization of the insertion area and increase the risk of catheter-related infection. As is known the humidity level of Indonesia with other countries is higher and the results of positive swabs in the insertion area are associated with Percutaneous Central Venous Catheter (PCVC) colonization and Catheter-related Sepsis (CRS). Transparent polyurethane and plaster gauze are two types of dressings that are different and often used. The transparent polyurethane is widely used in invasive procedures, there are still many medical staff who use plaster gauze dressings. The purpose of this study is to determine the difference in the number of germs in the CVC insertion area that are dressed using transparent polyurethane and plaster gauze. The design of this study is a quasi-experimental pretest-posttest control group with positive sampling. The number of samples is 12 for the intervention group and 11 for the control group. The intervention group performed transparent polyurethane dressings and a control group with plaster gauze. Calculation in the number of germs is with the cup count method. Wilcoxon and Mann-Whitney tests are for te data analysis. Based on the results of the study, it can be concluded that there is no difference in the number of CVC insertion germs between the use of dressings transparent polyurethane and plaster gauze so that both types of dressings can be used for CVC dressings in critical patient care settings.